Recurrent heat stroke in a runner: race simulation testing for return to activity - Roberts, W. O.; Dorman, J. C.; Bergeron, M. F. (Medicine & Science in Sports & Exercise, 2016)
ABSTRACT: Exertional heat stroke (EHS) occurs in distance runners and is a life-threatening condition. A 30-yr-old healthy recreational male distance runner (CR) collapsed at the 12-mile mark in two half marathon races 6 wk apart in fall 2009. In both episodes, CR was found on the ground confused, incoherent, sweaty, and warm to touch. The emergency medical team responded, and he was treated empirically for suspected EHS by cooling en route to the emergency department. In the emergency department, rectal temperatures were 40°C and 40.5°C for each episode, respectively. The first race start temperature was 16°C with 94% relative humidity (RH), and the second was 3°C, 75% RH. Heat tolerance test was within the normal range indicating low EHS risk. A race simulation test (environmental chamber, 25°C, 60% RH) at a treadmill pace of 10.5-12.9 km/h was stopped at 70 min coincident with a rectal temperature of 39.5°C. CR`s body weight dropped 3.49 kg with an estimated sweat loss of 4.09 L and an estimated total sweat Na+ loss of 7610 mg. We recommended that he limit his runs to <1 h and replace salt and fluid during and (mostly) after activity, run with a partner, acclimate to heat before racing, and reduce his pace or stop at the first sign of symptoms. Race simulation testing should be considered in athletes with recurrent EHS to assist with the return-to-activity recommendation.